(Partial) privatization social security: The Chilean model - a lesson to follow? - Roland Eisen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2000)
This paper examines thoroughly the Chilean Pension Reform, giving first an overview of the mandatory saving plan, the relevant institutions, and the rules for transition from the old to the new system. The main part of the paper contains a critical evaluation of the reform, in particular the macroeconomic performance with respect to capital formation and growth, and the effects on the savings rate as well as on the rates of return and labor market are discussed. Furthermore, the development of capital markets is reviewed. A short critique is presented with respect to intergenerational distribution and risk sharing as well as with respect to the social consequences.
urn:nbn:de:hebis:30-9776
Keywords: H55; 330; Privatization; Social Security reform; Chile